Incomes, inequality, and poverty in Kenya: A long-term perspective - Arne Bigsten; Damiano Kulundu Manda; Germano Mwabu; Anthony Wambugu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper seeks to measure and explain changes in incomes, inequality, and poverty in Kenya. It starts from a very long-term perspective covering the last century, but then focuses on a more detailed analysis of the recent period for which data from household surveys are available. We seek to provide consistent estimates of what has happened to national income, inequality and poverty over time, and to explain why they evolved in the way they did. We relate changes in inequality and poverty to changes in factor endowments and changes in economic and employment structures. We also provide some policy conclusions.
Keywords: I32; N37; O55; 330; endowments; employment; growth inequality; Kenya; poverty